PARENTS’ (IR)RESPONSIBILITY FOR SHARENTING (REMUNOM, 2024)
This work demonstrates the (ir)responsibility of parents or guardians of children and adolescents in the face of sharenting, an English term used for overexposure by parents or guardians through social networks. The use of the virtual world is heading towards overexposure of the lives of its users. It is common to see people on social media sharing various moments of their lives, including posting photos and videos of minors who are under their care. The legal problem to be faced is established through the clash of parents' duty to protect the physical and mental integrity of children and adolescents in their development and exaggerated sharing on social networks under the focus of (ir)responsibility. The present study was carried out using an exploratory methodology in the bibliographic field, which consisted of reviewing the literature related to the topic covered in the article. For this, understandings of doctrines, articles and texts published on the internet were used. The research aims to understand whether accountability occurs and how it can be sought through protection bodies. It is extremely important to discuss the topic because through research it will be possible to understand overexposure and thus implement the protection established by law for children and adolescents, protecting their physical and mental integrity.